2008
DOI: 10.1243/13506501jet342
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue mechanics of TiC-based cemented carbides

Abstract: The aim of this work was to investigate fracture and fatigue behaviour of TiC-Ni/Fe cermets under monotonic and cyclic loading.The fracture toughness K Ic was determined by a conventional testing method (using single edge notched beam) and evaluated by an indentation technique (indentation fracture toughness (IFT)). Results from both experimental routines were analysed and compared with the reference hardmetal -WC-10 wt% Co. As the result, a novel sequence for estimation of the IFT for TiC-and WC-based cemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In general, they correspond to actions much more limited in scope, from a fatigue perspective, than the referred program. All these studies have somehow confirmed already established cyclic stress effects on hardmetals (Ferreira, Pina Amaral, Antunes, & Costa, 2009;Gee, Mingard, & Roebuck, 2009;Ishihara, Goshima, Yoshimoto, & Sabu, 1999;Klaasen, Kübarsepp, Tsinjan, & Sergejev, 2011;Kluensner et al, 2009;Klünser et al, 2010;Li, Zhao, Wang, Gao, & Tang, 2013;Roebuck, 2002;Roebuck, Maderud, & Morrell, 2008;Roebuck, Mingard, Nordenstrom, & Halling, 2009;Sakagami, Kouno, & Yamamoto, 2007;Sakagami & Yamamoto, 2006;Sergejev, Preis, Hussainova, & Kübarsepp, 2008;Sergejev, Preis, Kübarsepp, & Antonov, 2008), but some of them include interesting new findings and approaches. For instance, Klünser et al (Kluensner et al, 2009;Klünser et al, 2010) reported for different WC-Co alloys the existence of ratcheting behavior in their cyclic stress-strain curve, determined under uniaxial compression loading for stress ratios of À1 and À3, and applied compressive stresses above the elastic limit.…”
Section: Strength Degradation Under Cyclic Loadssupporting
confidence: 53%
See 1 more Smart Citation
“…In general, they correspond to actions much more limited in scope, from a fatigue perspective, than the referred program. All these studies have somehow confirmed already established cyclic stress effects on hardmetals (Ferreira, Pina Amaral, Antunes, & Costa, 2009;Gee, Mingard, & Roebuck, 2009;Ishihara, Goshima, Yoshimoto, & Sabu, 1999;Klaasen, Kübarsepp, Tsinjan, & Sergejev, 2011;Kluensner et al, 2009;Klünser et al, 2010;Li, Zhao, Wang, Gao, & Tang, 2013;Roebuck, 2002;Roebuck, Maderud, & Morrell, 2008;Roebuck, Mingard, Nordenstrom, & Halling, 2009;Sakagami, Kouno, & Yamamoto, 2007;Sakagami & Yamamoto, 2006;Sergejev, Preis, Hussainova, & Kübarsepp, 2008;Sergejev, Preis, Kübarsepp, & Antonov, 2008), but some of them include interesting new findings and approaches. For instance, Klünser et al (Kluensner et al, 2009;Klünser et al, 2010) reported for different WC-Co alloys the existence of ratcheting behavior in their cyclic stress-strain curve, determined under uniaxial compression loading for stress ratios of À1 and À3, and applied compressive stresses above the elastic limit.…”
Section: Strength Degradation Under Cyclic Loadssupporting
confidence: 53%
“…Although the use of notched specimens by the National Physics Laboratory's (NPL's) group is rather focused on the evaluation of the thermomechanical fatigue response of cemented carbidesdas originally aimed (Roebuck & Gee, 1996;Dary, Roebuck, & Gee, 1999), and corresponding results to be commented in a later sectiondit clearly represents an interesting complementary testing methodology for evaluating and understanding microstructural effects on these materials. Notched specimens have also been employed in several studies recently, although following different objectives: assessment of fatigue notch sensitivity of cermets (Sergejev, Preis, Hussainova, et al, 2008), evaluation of high-temperature fatigue strength (Ferreira et al, 2009), and analysis of microstructural effects on fatigue behavior (Li et al, 2013). The results presented in these studies are promising regarding suitability of using notched specimens for assessing microstructural effects on fatigue response under service-like conditions, i.e.…”
Section: Strength Degradation Under Cyclic Loadsmentioning
confidence: 99%
“…The deviations of the results are quite large as it could be expected for such a complicated system as a ceramic-metal composite. However, for the qualitative assessment of the cermet properties indentation method gives quite reasonable results [9].…”
Section: Materials and Characterizationmentioning
confidence: 99%
“…The cemented carbide fatigue crack growth is linearly increases on threshold of cemented mean carbide grain size and mechanism of crack deflection ismore effective action for fatigue growth mechanisms [39] therefore coarsed hard metals are normally sensitive to fatigue behavior rather than binder mean free path which has fine-graded materials [23], [24]. From this observation, it is clear that individual deliberation of collective effects about altering binder content of carbide grain size is very important for the existence of different approaches between monotonic loading properties as considered for comparison [40].…”
Section: Fatigue Behavior Of Cemented Carbidementioning
confidence: 99%
“…These outstanding mechanical properties results from extremely different properties of two interpenetrating phases (brittle and ductile metallic phase) [46]. Within brittle carbide the main cause of wear in cutting tools is observed in microscopic images where observations can be done in abrasive wear of rake and flank surfaces [40]. The consequence of cemented carbides in wide range of extremely demanding material applications where performance of tribomechanical is very high and these needs improved reliability such as metal cutting, rock drilling and metal forming [44].…”
Section: Fatigue Behavior Of Cemented Carbidementioning
confidence: 99%